Solar-Powered Low-Cost Housing: Designing Off-Grid Communities with Interlocking Stabilised Soil Blocks (ISSB) - Obafemi A. IBITOYE; Jemimah O. TOLU-ALALADE (FUDMA Journal of Engineering and Technology, 2026)
This study explores the integration of solar photovoltaic (PV) systems with Interlocking Stabilised Soil Blocks (ISSB) to develop affordable, energy-efficient housing models for Nigeria’s off-grid communities. Using quantitative survey data from 424 respondents including architects, engineers, builders, and residents the research assessed awareness, perceived compatibility, affordability, and willingness to adopt ISSB–solar housing. Statistical analysis through chi-square, Pearson correlation, and ANOVA revealed a strong positive perception of ISSB–solar integration (mean = 4.12; SD = 0.78), with significant relationships between affordability and adoption (r = 0.52, p < .01) and between thermal comfort and energy efficiency (r = 0.47, p < .01). Over 70 % of participants affirmed that ISSB structures can safely support PV panels, and 65 % recognized reduced long-term energy costs despite higher initial investment. The findings demonstrate that coupling ISSB with solar systems enhances thermal comfort, promotes energy independence, and aligns with sustainable development goals. The study recommends financial incentives, technical capacity-building, and community-driven pilot projects to scale up solar-powered ISSB housing as a pathway toward resilient, low-carbon rural development in Nigeria.